1996
DOI: 10.1149/1.1837204
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and Formation of Porous GaAs

Abstract: The present work deals with localized dissolution processes (pit and pore initiation and growth) of p-and n-type (100) GaAs. Pit and pore growth can be electrochemically initiated on both conduction types in chloride-containing solutions and leads after extended periods of time to the formation of a porous GaAs structure. In the case of p-type material, localized dissolution is only observed if a passivating film is present on the surface, otherwise, e.g., in acidic solutions, the material suffers from a unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
119
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(121 citation statements)
references
References 2 publications
2
119
0
Order By: Relevance
“…Schmuki et al 38 were found to both occur at a potential region that is near −0.8 V vs SCE until all the oxide was reduced. This value corresponds well with the one observed here in the initial part of the transient in Figure 4c, for the reduction of the Fe-rich oxide generated from step 2.…”
Section: Discussionmentioning
confidence: 99%
“…Schmuki et al 38 were found to both occur at a potential region that is near −0.8 V vs SCE until all the oxide was reduced. This value corresponds well with the one observed here in the initial part of the transient in Figure 4c, for the reduction of the Fe-rich oxide generated from step 2.…”
Section: Discussionmentioning
confidence: 99%
“…Anion type and concentration can play a significant role in affecting the pore growth and morphology (6,7). The depth of porous layers and their preferential crystallographic growth directions have been shown to be affected by the substrate type (8), orientation (9) and doping density (10).…”
Section: Introductionmentioning
confidence: 99%
“…The photocurrents of the porous electrode measured in the NaCl electrolyte are plotted in Figure 4(a). In these measurements, the light intensity was set to 2 mW/cm 2 , and the applied voltage, V a , was swept in the positive direction from -0.5 V to 2.5 V. The peaks of anodic current observed at around 0.2 V, which were even observed under the dark condition, are probably caused by the reverse reaction H 2 -> 2H + + 2e -. In contrast to the photocurrents measured in FSI mode, the photocurrents obtained with wavelength of 360 nm showed the smallest values.…”
Section: Photocurrent Measurements Of Gan Porous Structures In Fsi Anmentioning
confidence: 99%